Effect of pasture rest on nematode larvae availability in the Pantanal region of Mato Grosso - Catto, João Batista (Pesquisa Agropecuaria Brasileira, 2014)
Monthly, during a four-month period, after middle March (end of the rainy season), two tracer weaned calves were put in a rested paddock and were later necropsied. During the experimental period, pasture was also examined for presence and number of infestant larvae. On direct examination, the pasture was positive until three months after rest and through the animal examination on the four months of the study. It was concluded that let the pasture rest for two months during or at the end of the rainy season strongly reduced the availability of larvae on the pasture.